Pengaruh Keamanan,Kesehatan Kerja Terhadap Kinerja Karyawan di PT. Raihan Cipta Abadi - Hermin Andi Magga (Jurnal Online Manajemen ELPEI, 2023)
This study aims to determine the effect of safety, occupational health on employee performance at PT.Raihan Cipta Abadi. The research method used in this study is a quantitative approach. The population in this study were all employees of PT.Raihan Cipta Abadi. The sampling technique used is saturated sampling where the entire population is a sample of 57 people. Data collection techniques using a questionnaire. The collected data is processed using SPSS. Based on the results of the study it was concluded that the security variable (X1) has a significant effect on employee performance (Y) partially as evidenced by a sig value of 0.026 <0.05. And the variable health  (X2) is the variable that has the most significant effect on employee performance (Y) partially as evidenced by a significance value of 0.030 <0.05. Therefore, in this study hypotheses 1, 2 and 3 are accepted. It is recommended that companies provide encouragement to employees and pay attention to the safety and health of their employees.